Case report: Immunotherapy inducing unexpected overall survival in choroidal melanoma: about a case - Elhaitmy, Youssef; El Anssari, Soukaina; Fournel, Pierre; Mellas, Nawfel; Bouleftour, Wafa; Lamuraglia, Michele (Frontiers in Oncology, 2024)
Choroidal melanoma (CM) is the most common malignant ocular tumor in adults. The current treatment of metastatic CM is limited by the intrinsic resistance of CM to conventional systemic therapies. Immunotherapy alone or in association with cytotoxic treatment became a realist option treatment. Advancements in molecular biology have resulted in the identification of a number of promising prognostic and therapeutic targets. Herein, we report a rare case of 36-year-old patient with metastatic CM who presented a good long response to treatment with double immunotherapy reaching 3 years of overall survival, which has never been described in the literature.